Quality in peruvian education, a social requirement - Aroquipa Durán, Yolanda (2019)
The current society demands a quality education, a widespread voice throughout the world, so in this article are show theoretical contributions on the demands of society; towards the MINEDU, Educational Institutions and teachers, quality assessment; highly criticized, which only considers notes and some complaints for the sale of notes, we also deal with quality control; which demands a radical change in all educational agents. Concluding that the demands of society must be met by educational entities, assuming a commitment to develop a change towards quality at all levels.